How Does the Sweet Violet (Viola odorata L.) Fight Pathogens and Pests – Cyclotides as a Comprehensive Plant Host Defense System - Slazak, Blazej; Kapusta, Małgorzata; Strömstedt, Adam A.; Słomka, Aneta; Krychowiak, Marta; Shariatgorji, Mohammadreza; Andrén, Per E.; Bohdanowicz, Jerzy; Kuta, Elżbieta; Göransson, Ulf (Frontiers in Plant Science, 2018)
Cyclotides are cyclic plant polypeptides of 27-37 amino acid residues. They have been extensively studied in bioengineering and drug development contexts. However, less is known about the relevance of cyclotides for the plants producing them. The anti-insect larvae effects of kB1 and antibacterial activity of cyO2 suggest that cyclotides are a part of plant host defense. The sweet violet (Viola odorata L.) produces a wide array of cyclotides, including kB1 and cyO2, with distinct presumed biological roles. Here, we evaluate V. odorata cyclotides’ potency against plant pathogens and their mode of action using bioassays, liposome experiments and immunogold labeling for transmission electron microscopy (TEM). We explore the link between the biological activity and distribution in plant generative, vegetative tissues and seeds, depicted by immunohistochemistry and matrix assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI). Cyclotides cyO2, cyO3, cyO13, and cyO19 are shown to have potent activity against model fungal plant pathogens (Fusarium oxysporum, Fusarium graminearum, Fusarium culmorum, Mycosphaerella fragariae, Botrytis cinerea) and fungi isolated from violets (Colletotrichum utrechtense and Alternaria alternata), with minimal inhibitory concentrations (MICs) ranging from 0.8 µM to 25 µM. Inhibition of phytopathogenic bacteria – Pseudomonas syringae pv. syringae, Dickeya dadantii and Pectobacterium atrosepticum – is also observed with MIC = 25–100 µM. A membrane-disrupting antifungal mode of action is shown. Finding cyO2 inside the fungal spore cells in TEM images may indicate that other, intracellular targets may be involved in the mechanism of toxicity. Fungi can't break down cyclotides in the course of days. varv A (kalata S) and kB1 show little potency against pathogenic fungi when compared with the tested cycloviolacins. cyO2, cyO3, cyO19 and kB1 are differentially distributed and found in tissues vulnerable to pathogen (epidermis, rizodermis, vascular bundles, protodermis, procambium, ovary walls, outer integuments) and pest (ground tissues of leaf and petiole) attacks, respectively, indicating a link between the cyclotides’ sites of accumulation and a biological role. Cyclotides emerge as a comprehensive defense system in V. odorata, in which different types of peptides have specific targets that determine their distribution in plant tissues.